The initial experience with RENAL nephrometry in children, adolescents, and young adults with renal tumors. Issue 8 (9th March 2014) - Cost, Nicholas G.; DeFoor, W. Robert; Crotty, Eric J.; Geller, James I.
Abstract Background No standardized manner exits to objectively compare renal tumor complexity in children and adolescents. However, the RENAL Nephrometry scoring system has been recently developed in adults and shown to predict tumor complexity and correlate with clinical outcomes. Thus, the study objective was to evaluate RENAL Nephrometry tumor score in a population of children, adolescents, and young adults and correlate it with tumor features and pathology. Methods Patients at the study institution who underwent attempted renal tumor resection from 2002 to 2012, and had pre‐operative imaging available for scoring were retrospectively reviewed. A Nephrometry score for each affected kidney was calculated separately by two blinded reviewers and the final score was based on consensus review. Tumor characteristics and oncologic outcomes were compared between the low‐, moderate‐, and high‐complexity masses. Results Sixty‐five patients and 67 kidneys met study criteria. This included: 5 (7.5%) low‐complexity, 11 (16.4%) moderate‐complexity, and 51 (76.1%) high‐complexity lesions. In comparing the clinical and pathologic features between groups, it was observed that less complex masses were observed in older patients, were more commonly managed with nephron‐sparing surgery, and more often represented renal cell carcinoma (RCC) and other non‐Wilms tumor pathology. No statistically significant correlation was observed between tumor complexity score and blood loss, operative time, transfusion requirement, positive margins or tumor rupture. Conclusion In general, renal lesions in this population are highly complex. In its current form, RENAL Nephrometry appears most useful in evaluating tumor complexity in RCC and masses in older children and adolescents. Pediatr Blood Cancer 2014; 61:1434–1439. © 2014 Wiley Periodicals, Inc.